Water & wastewater: Green efficiency ensures consistent water supply. Issue 5 (September 2015) - Unknown
Abstract : When the United States city of Delaware decided to introduce a new water treatment system, the challenge was to ensure a reliable, potable supply to a population of more than 900, 000 people using the most efficient and environmentally friendly techniques and equipment available. As a result, it employed H2 O Innovation and Professional Water Technologies, to deliver the desired result.